Factors Affecting the Enrollment of Criminology at King’s College of the Philippines - Gambulao Jr., Ruben M.; Depayso, Dempsey O. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
College enrollment is an important decision for all aspiring students of higher education. This study investigates the factors affecting the enrollment of freshmen college students at King’s College of the Philippines-College of Criminal Justice Education (KCP-CCJE). Data has been collected through questionnaire. Mean and percentage were used to determine the main reasons of the respondents. Selected factors were ranked by the respondents from their most reasons and least reason from 1-10. The sample size was 191, consisting of freshman students who have enrolled during the first semester of Academic year 2020-2021. Results showed that academic program, college reputation, and influence from others are the most reason of the respondents in enrolling in the college.